Identification of autoantigens and their potential post-translational modification in EGPA and severe eosinophilic asthma - Esposito, Ilaria; Kontra, Ioanna; Giacomassi, Chiara; Manou-Stathopoulou, Sotiria; Brown, James; Stratton, Richard; Verykokou, Galateia; Buccafusca, Roberto; Stevens, Michael; Nissim, Ahuva; Lewis, Myles J.; Pfeffer, Paul E. (Frontiers in Immunology, 2023)
Background: The chronic airways inflammation in severe eosinophilic asthma (SEA) suggests potential autoimmune aetiology with unidentified autoantibodies analogous to myeloperoxidase (MPO) in ANCA-positive EGPA (eosinophilic granulomatosis with polyangiitis). Previous research has shown that oxidative post-translational modification (oxPTM) of proteins is an important mechanism by which autoantibody responses may escape immune tolerance. Autoantibodies to oxPTM autoantigens in SEA have not previously been studied. Methods: Patients with EGPA and SEA were recruited as well as healthy control participants. Autoantigen agnostic approach: Participant serum was incubated with slides of unstimulated and PMA-stimulated neutrophils and eosinophils, and autoantibodies to granulocytes identified by immunofluorescence with anti-human IgG FITC antibody. Target autoantigen approach: Candidate proteins were identified from previous literature and FANTOM-5 geneset analysis for eosinophil expressed proteins. Serum IgG autoantibodies to these proteins, in native and oxPTM form, were detected by indirect ELISA. Results: Immunofluorescence studies showed serum from patients with known ANCA stained for IgG against neutrophils as expected. In addition, serum from 9 of 17 tested SEA patients stained for IgG to PMA-stimulated neutrophils undergoing NETosis. Immunofluorescent staining of eosinophil slides was evident with serum from all participants (healthy and with eosinophilic disease) with diffuse cytoplasmic staining except for one SEA individual in which subtle nuclear staining was evident. FANTOM-5 geneset analysis identified TREM1 (triggering receptor expressed on myeloid cells 1) and IL-1 Receptor 2 (IL1R2) as eosinophil specific proteins to test for autoantibody responses in addition to MPO, eosinophil peroxidase (EPX) and Collagen-V identified from previous literature. Indirect ELISAs found high concentrations of serum autoantibodies to Collagen-V, MPO and TREM1 in a higher proportion of SEA patients than healthy controls. High concentrations of serum autoantibodies to EPX were evident in serum from both healthy and SEA participants. The proportion of patients with positive autoantibody ELISAs was not increased when examining oxPTM compared to native proteins. Discussion: Although none of the target proteins studied showed high sensitivity for SEA, the high proportion of patients positive for at least one serum autoantibody shows the potential with more research for autoantibody serology to improve diagnostic testing for severe asthma.